2007
DOI: 10.1242/dev.009597
|View full text |Cite
|
Sign up to set email alerts
|

TRICHOMELESS1 regulates trichome patterning by suppressingGLABRA1inArabidopsis

Abstract: The patterning of epidermal cell types in Arabidopsis is a simple and useful model for studying the molecular basis of cell specification in plants. The distribution of different cell types in the Arabidopsis epidermis is regulated by a lateral inhibition mechanism that relies on interactions between transcription factors. However, it is unclear how temporal-or organ-specific differences in epidermal patterning are achieved. Here we identify TRICHOMELESS1 (TCL1) as a new and major single-repeat MYBtype transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
260
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(269 citation statements)
references
References 43 publications
(92 reference statements)
5
260
0
2
Order By: Relevance
“…[14][15][16][17][18] Five of these closely related R3-MYBs, namely CPC (CAPRICE), TRY (TRIPTYCHON), ETC1 (ENHANCER OF CAPRICE AND TRIPTYCHON1), ETC2, and ETC3, are capable of interacting with the bHLH proteins GL3, EGL3, and TT8 to counteract the transcriptional activity of the MBW complex by sequestering its bHLH component. 16,17 Another related R3-MYB protein, TCL1 (TRICHOMELESS1), can be recruited to the cis-acting regulatory elements of GL1 to inhibit its transcription and thus negatively regulates trichome formation.…”
Section: Mybl2 Inhibits the Activity Of The Mbw Complex And Negativelmentioning
confidence: 99%
“…[14][15][16][17][18] Five of these closely related R3-MYBs, namely CPC (CAPRICE), TRY (TRIPTYCHON), ETC1 (ENHANCER OF CAPRICE AND TRIPTYCHON1), ETC2, and ETC3, are capable of interacting with the bHLH proteins GL3, EGL3, and TT8 to counteract the transcriptional activity of the MBW complex by sequestering its bHLH component. 16,17 Another related R3-MYB protein, TCL1 (TRICHOMELESS1), can be recruited to the cis-acting regulatory elements of GL1 to inhibit its transcription and thus negatively regulates trichome formation.…”
Section: Mybl2 Inhibits the Activity Of The Mbw Complex And Negativelmentioning
confidence: 99%
“…TTG1, GL1, and GL3+EGL3 encode a WD40 protein, an R2R3 MYB transcription factor, and two basic helix-loop-helix-type transcription factors, respectively, and they form a ternary complex that initiates trichome cell development by activating GL2, which encodes a homeodomain/leucine zipper t ranscription factor (Rerie et al, 1994;Masucci et al, 1996;Schiefelbein, 2003;Pesch and Hü lskamp, 2004;Ramsay and Glover, 2005). Another group of genes encode the single-repeat R3 MYB factors TRIPTYCHON (TRY), CAPRICE (CPC), ENHANCER OF TRY AND CPC1 (ETC1), ETC2, ETC3, and TRICHOMELESS1 (TCL1) (Wada et al, 1997;Esch et al, 2004;Kirik et al, 2004aKirik et al, , 2004bSchellmann et al, 2002;Simon et al, 2007;Wang et al, 2007). They suppress trichome initiation in a redundant manner, although TRY, TCL1, and CPC exert a major influence on rosette leaves, inflorescences, and roots (root hairs), respectively (Wada et al, 1997;Schnittger et al, 1998;Schellmann et al, 2002;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Another group of genes encode the single-repeat R3 MYB factors TRIPTYCHON (TRY), CAPRICE (CPC), ENHANCER OF TRY AND CPC1 (ETC1), ETC2, ETC3, and TRICHOMELESS1 (TCL1) (Wada et al, 1997;Esch et al, 2004;Kirik et al, 2004aKirik et al, , 2004bSchellmann et al, 2002;Simon et al, 2007;Wang et al, 2007). They suppress trichome initiation in a redundant manner, although TRY, TCL1, and CPC exert a major influence on rosette leaves, inflorescences, and roots (root hairs), respectively (Wada et al, 1997;Schnittger et al, 1998;Schellmann et al, 2002;Wang et al, 2007). It was suggested that expression of some of the negative regulator genes, including TRY, CPC, ETC1, and ETC3, was completely or partially dependent on the GL1-GL3-TTG1 protein complex (Morohashi et al, 2007), whereas TCL1 and ETC2 were regulated by yet unidentified mechanisms (Wang et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The WER/ MYB23 and EGL3/GL3 proteins appear to participate in a multimeric transcriptional regulatory complex with the TTG WD-repeat protein to induce non-hair cell differentiation, as well as expression of the TRY/CPC one-repeat Mybs (Lee and Schiefelbein, 1999;Ryu et al, 2005;Wang et al, 2008). The family of one-repeat Mybs engages in a lateral inhibition mechanism by moving from cell to cell and hindering formation of the MYB23/WER-EGL3/GL3-TTG complex, which permits expression of hair cell differentiation genes (Wada et al, 1997;Schellmann et al, 2002;Kurata et al, 2005;Tominaga et al, 2007;Wang et al, 2007Wang et al, , 2008Song et al, 2011). The relative abundance of the MYB23/WER-EGL3/GL3-TTG transcriptional complex in the presumptive hair cells and non-hair cells of the developing root epidermis appears to be controlled by cell position-dependent SCRAMBLED receptor kinase signaling (Kwak et al, 2005;Kwak and Schiefelbein, 2008;Savage et al, 2008).…”
Section: Introductionmentioning
confidence: 99%